Wireless Sensor Network Implementation for IoT-Based Environmental Security Monitoring. Issue 1 (June 2020) - Hendra, A; Palantei, E; Syafaruddin,; Hadis, M S; Zulkarnaim, N; Mansyur, M F
Abstract: The use of Wireless Sensor Network (WSN) technology with Internet of Things (IoT) technology has been developed. Internet of Things (IoT) is a technology that enables control, communication and collaboration with various hardware devices over computer networks. The Internet of Things (IoT) has been a form of transformation and development of information technology and Internet networks. This article uses IoT-based environmental monitoring networks to monitor environmental safety in real time. The proposed WSN network is structured to allow continuous monitoring of environmental safety and environmental issues, such as: For example, the potential risk of fire or crime in the environment and many others. In practice, the WSN network consists of sensors and local servers connected via the Internet. The generated data comes from several electronic sensors, such as proximity sensors and fire sensors, all of which are connected to the local server via the gateway. A number of interesting experimental results, including the analysis of energy consumption, are discussed in detail.